Study on the corrosion of carbon steel pipe upon different type of soils - Heng, Cheng Liang (2014)
Pipelines are one of the economical ways to transport large quantities of fluids such as natural gas, oil and others. However pipelines for transportation need to consider factors such as strength of material, cost, corrosion caused by carrier fluid and soil properties on corrosion. It is essential to have knowledge about the soils which may cause corrosion to the pipelines. Analysis on the soils are done for investigate the physical properties such as structure or texture and permeability of soils and also the chemical properties for example soil pH and conductivity. Structure of soil is studied by using sedimentation separation method to distinguish weight percent of clay, sand and silt. Permeability of soil is determined by constant head and falling head permeability test. Soil chemical properties are determined by pH meter and conductivity meter. Corrosion rate can be determined by weight-loss method that determined the metal loss during corrosion. Moisture content of soils is determined by weighting initial and final weight after drying in oven. One-way ANOVA test of the corrosion data with factor which type of soil showed that the model developed is limited to certain type soil. Result analysis will be done by linear and non-linear correlation regressions such as Weibull and exponential growth and decay to study the relationships of corrosion rate with time. Result of comparison of three curve fitting method showed that clay and silty clay loams is moderately fitted with exponential fit, while sand and silt is largely deviated from all three curve fit method. Trend analysis result of soil type clay and silty clay loam only can be used to model the correlation dynamic for corrosion control with reasonable accuracy. Corrosion model developed from averaged observed data yield unsatisfied fit of model to observed data. However, by further eliminate extreme observed data for each month for each type of soils the adjusted exponential model for all type of soil yield high R2 value